Development of time delay current control for lead acid battery 12 v DC by using arduino - Mat Yatim, Nurul Syazrah (2014)
Development of time delay current control for lead acid battery 12 V dc by using Arduino is the aim of this thesis. The development problem is necessary before applying control techniques to guarantee the execution of any task according to a desired input with minimum error. The main objective of this thesis is to design the time delay has on the performance of a current controlled for the buck-boost converter. The time delay controller is generally regarded as a nuisance to a control system. In addition, the performance of the Arduino and MATLAB as a signal processing device interface time is used. The feedback of open loop and closed loop time delay controller is also been analyzed. Based on results, the experiment of closed loop hardware gives better results than simulation in terms of output current. Through this study it is proved that the time delay controller is successfully designed to control current for lead acid battery.